Mechanism of arsenic uptake, translocation and plant resistance to accumulate arsenic in rice grains - Suriyagoda, Lalith D.B.; Dittert, Klaus; Lambers, Hans (Agriculture, ecosystems & environment, 2018)
•Of the total grain As, 54% is composed of inorganic As.•Soils containing over 5.5mg As kg−1 have risk of accumulating grain [As] above WHO-permissible limit.•Higher radial oxygen loss, and formation of iron plaques reduce As uptake.•Once taken up, As- reduction, complexation and sequestration in vacuoles reduce As translocate to grains.•Grain As speciation is affected by location in the grain, forms of As species, grain-filling stage and geographic origin. A global data analysis shows that rice grain arsenic (As) concentrations increase with increasing soil As concentrations until about 60mg As kg−1soil and then decreases. Of the total grain As, 54% is composed of inorganic As. Therefore, when considering the WHO-permissible grain inorganic As concentration, i.e. 0.2mg As kg−1, the permissible grain total As concentrations is 0.37mg total As kg−1grain. Soil total As concentration when grain total As concentration reaches permissible level is 5.5mg As kg−1soil. Therefore, the suitable soil As concentrations for screening rice cultivars in rice agroecosystems for As resistance is 5–60mg As kg−1soil. Rice has traits to reduce uptake and translocation of As to grains. Cultivars with higher root porosity, radial oxygen loss, or formation of iron plaques bind more As to iron plaques, reducing As uptake (i.e. As avoidance). Once taken up, glutathione/glutaredoxin-mediated As reduction, and phytochelatin-dependent complexation and sequestration in vacuoles result in less translocation of As to the grain. Moreover, generation of reactive oxygen species and the production of antioxidant enzymes further reduce As toxicity (i.e. As resistance). These resistance mechanisms in rice agroecosystems are further enhanced when adequate concentrations of silicon and sulfur are present in soils and tissues, and when plants are associated with arbuscular mycorrhizal fungi, particularly under aerobic or intermittent-aerobic soil condition. Therefore, As concentrations in rice ecosystems decrease in the order of: roots > leaves > grains, and in grains: hull > bran polish > brown rice > raw rice> polished rice > cooked rice. Within the grain, As speciation is affected by the location in the grain, forms of As species, the grain-filling stage, geographic origin, ecosystem management and cultivars used. Indica type accumulates more As in their grains than japonica type. Rice grain production, within safe limits of As, requires the consideration of soil As dynamics including soil management, cultivar responses including uptake and translocation, and post-harvest processing techniques.